PENGARUH CURRENT RATIO, PRICE TO BOOK VALUE, DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP RETURNSAHAM (Studi Empiris Pada Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Erika Nona Septiani, 14.05.52.0030; Aini, Nur (Students' Journal of Accounting and Banking, 2018)
ABSTRACT This study examines and analyzes the influence of Current Ratio, Price to Book Value, Debt to Equity Ratio and Return On Asset on Stock Return. The population in this study in the sector food and beverage which are listed in Indonesia Stock Exchange in years 2012 until 2016. The samples selections are using purposive sampling with period of research year 2012 until 2016. Analyzes influence between variable by using method of multiple linear regression analysis. The result of this study indicatethatCurrent Ratio and Debt to Equity Ratiohas a significant positive effect on theStock Return.Price to Book Value, and Return On Asset do not affect the disclosure ofStock Return. Keywords: Stock Return, Current Ratio, Price to Book Value, Debt to Equity Ratio, and Return On Asset